1975
DOI: 10.3109/00016357509004620
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride and dental age

Abstract: The dental ages of 149 children born and grown up in a district with naturally occurring fluoride in the drinking water (maximum level 2.0 mg/l) were compared with those of 181 control children born and grown up in a neighbouring low-fluoride district (less than or equal to 0.1 mg/l). The children were 9--12 years old. In neither group did the dental ages prove to differ from normality. It is concluded that concentrations below the highest recommended level fluoride occurring naturally in the drinking water do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

1977
1977
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 5 publications
0
17
0
Order By: Relevance
“…The results of these studies showed that consumption of xylitol reduced the growth of dental plaque in participating dental students by up to 50% compared with use of sucrose, D -glucose, or D -fructose [11, 12]. Based on these observations, a two-year clinical caries study and a one-year chewing-gum trial (collectively called the Turku Sugar Studies) were set up in 1972-1973 [13]. The results showed that xylitol consumption was associated with an impressive caries reduction and prompted other researchers to repeat the Turku studies.…”
Section: Clinical Caries Trials On Sugar Alcoholsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of these studies showed that consumption of xylitol reduced the growth of dental plaque in participating dental students by up to 50% compared with use of sucrose, D -glucose, or D -fructose [11, 12]. Based on these observations, a two-year clinical caries study and a one-year chewing-gum trial (collectively called the Turku Sugar Studies) were set up in 1972-1973 [13]. The results showed that xylitol consumption was associated with an impressive caries reduction and prompted other researchers to repeat the Turku studies.…”
Section: Clinical Caries Trials On Sugar Alcoholsmentioning
confidence: 99%
“…Four-day use of xylitol as a sweetener in subjects' diet resulted in about 50% reduction in plaque compared with the use of sucrose. The strong plaque mass-reducing effect of xylitol along with supportive biochemical effects observed in plaque in 1970-1971 [11, 12] generated first the Turku Sugar Studies [13] and next all other xylitol caries trials shown in Table 1 Figure 1…”
Section: Clinical Caries Trials On Sugar Alcoholsmentioning
confidence: 99%
“…Scheinin et al [1964] and Miller [1965] confirmed these data but also found a tendency toward delayed erup tion of the second molars, which could not be directly influenced by deciduous denti tion. However, with F concentrations in wa ter at optimum or slightly above differences in eruption patterns have been small or in significant in several investigations [Kunzel, 1971;Binder, 1972;Grahnen et al, 1975]. The eruption of the deciduous dentition seems to be unaffected by F [Tank and Storwick, 1964], or even slightly accelerat ed by optimum water F concentration [Cas taldi et al, 1969].…”
Section: Early Developm Ent O F Stu D Ie S On F/caries Relationshipmentioning
confidence: 99%
“…Most research on the etiology of caries focuses on individual-level factors such as oral hygiene (17), salivary flow (18), diet (19), genes (20), or environmental exposures causing developmental defects of enamel (21, 22). According to Rose, however, “to find the determinants of prevalence and incidence rates, we need to study characteristics of populations, not characteristics of individuals” (23).…”
Section: Discussionmentioning
confidence: 99%